Economic incentives for adopting irrigation innovations in arid environments - Bekchanov, Maksud; Lamers, John P.A.; Nurmetov, K. (2014)
Water is getting scarce in many parts of the world, consequently challenging researchers, policy makers and practitioners to design options for a more efficient use of these resources, especially in irrigated agriculture. Although technical-economic efficiency of potential water-wise options and institutional restrictions for their implementation in the developing and less-developed countries are well documented, little evidence exists about the incentives for farmers and regional development agencies to adopt the efficient irrigation innovations. A linear programming model for optimizing regional agricultural income was developed to analyze the impact of water availability, water pricing, and investment accessibility on water-wise innovation adoption and conveyance efficiency improvement. The model was applied to the case of Khorezm, a region in northwestern Uzbekistan that is part of the downstream Amu Darya River in the Aral Sea Basin. Model results indicate that improving conveyance efficiency is economically less attractive than improving field-level water use efficiency due to enormous investment costs for lining the canals. Water-wise options such as manuring cotton and potatoes, implementing hydrogel in wheat and cotton, and drip irrigation of melons and vegetables are among the most promising field-level improvement options to gain optimal regional incomes under decreased water availability and increased water prices. It is illustrated that despite the huge investments needed for a wide-scale implementation of modern irrigation technologies such as drip irrigation and laser-guided land leveling, their adoption will substantially improve water use efficiency, while their implementation costs can be compensated for by the additional revenues due to increased yields and reduced costs.